Physical characteristics study of saw dust as liquid fuels application: article - Syed Osman, Syed Ahmad Alhaddad; Kasmuri, Nor Hazelah (2019)
The objective of this research is to analyses the characteristics of saw dust biomass as an alternative for liquid fuel application through analyzing of its physical properties (proximate analysis, heating value, Fourier-Transform Infrared Spectroscopy (FTIR) and thermogravimetric analysis (TGA)). Biomass was good solutions for an alternative for energy production due to its low cost, energy saving and environmental friendly. This study shows the usage saw dust biomass as an alternative for biofuel production towards the environment. The saw dust has high heating value of 3.0394 MJ/kg. Based from the proximate analysis, the saw dust has high volatile matter (60.47%), low fixed carbon content (21.71 %), low ash content (10.86 %) and low moisture content (6.96 %) which indicates it can be used as liquid fuel. On the other hand, FTIR analysis shows the result of the functional group obtains in the sample while TGA analysis produced the result on the mass loss achieved by saw dust sample during pyrolysis which is at 65.8% with high decomposition rate at 3.57 mg/min.